Rancang Bangun Chasis Gokart Dengan Beban Maksimum 100 Kg - PASARIBU, SABAR (Universitas Teknokrat Indonesia, 2024)
Gokart is one of the four-wheeled automotive sports such as Formula, NASCAR, Speed Car, Rally, Offroad and so on. Its small physical form, has a small engine power capacity as well so that gokarts only need a short track. The method used in this design is experimentation and literature. The gokart engine used is a motorcycle engine with a capacity of 100 cc. From the results of the chassis calculation, the engine weight is 23 kg with the engine load received by the left and right rear wheels of 23 kg each, the driver's weight is 70 kg and the load received by the wheels is 35 kg. There are quite a lot of types of gokart chassis, the gokart chassis I chose is Turbular space frame, the height of the frame is 100 mm from the ground. The performance of the go-kart has been tested with the following operating parameters: Braking and deceleration required with an initial speed of 2.8 (m/s) = 10.10 km/h by : 1030.32 (N), and the results of the turning behavior test found that the gokart experienced understeer. The results of testing the strength of the frame are known gokart able to withstand the load of the driver 100 kg.